Penerapan Penggunaan Alat-alat Perbengkelan Pada Bengkel Rita Jaya Motor Pesurungan Lor - Akhmadi, Amin Nur; Budi, Sigit Setijo; Ariyanto, Nur Aidi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
The potential use of workshop tools is often not in accordance with the SST and is related to speed work in work which includes servicing the carburetor, fuel system, steering system, electrical system so that in workshop work there are often delays in dealing with customers such as tune ups which should be handled quickly but with a lack of tools the work becomes late. Providing knowledge about existing equipment in workshops, providing skills in using multifunctional tools for repairs, improving the quality of human resources, especially mechanics. This service uses a direct, practical presentation method at the workshop where the chairman gives directions to customers and surrounding mechanics to take part in the training using multifunctional key tools. From this activity it can be found that in the workshop, when repairs are busy, customers really complain about how long it takes to repair their motorbikes because the equipment does not comply with operational procedures, and there are no SST tools. With community service activities at the Rita Motor Pesurungan Lor workshop, it provides knowledge, understanding and innovation regarding efficient and multi-functional workshop tools. Speed up employee work in service with this multi-functional tool so that customers are satisfied with its performance.